The management of Helicobacter pylori infection and prevention and control of gastric cancer in China - Hu, Yi; Zhu, Yin; Lu, Nong-Hua (Frontiers in Cellular and Infection Microbiology, 2022)
Helicobacter pylori (H. pylori) infection, a type-1 carcinogen, was closely associated with gastric cancer (GC). Successfully eradicating H. pylori infection could reduce the incidence of GC. China was a country with high incidence of GC and high prevalence of H. pylori infection. Nearly half of worldwide GC new cases and deaths attributed to H. pylori infection occurred in China. H. pylori prevalence varied over time with the improvement of socioeconomic status and sanitary conditions. The knowledge of antibiotic resistance rate in time was important to guide the clinical choice of antibiotics use in the regimens. With the publication of five Chinese consensus reports on the management of H. pylori infection and the effort of public preach of H. pylori-related knowledge, the standardization of H. pylori diagnosis and treatment by clinicians was improved. Bismuth-containing quadruple therapy was widely applied in clinical practice of H. pylori eradication because of high efficacy and safety. High-dose Proton Pump Inhibitor-amoxicillin dual therapy or vonoprazan-amoxicillin dual therapy showed comparable efficacy and lower side effects than bismuth-containing quadruple therapy, which were the alternative choice. The diagnosis rate of early GC was low and distinguishing Chinese GC risk population for the further endoscopy screening was important. Efforts have been done to establish prediction models to stratify GC risk in the Chinese GC risk population. We reviewed the current situation of the management of H. pylori infection and prevention and control of GC in China here.